1997
DOI: 10.1086/304702
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Stationary States of Dust Flows under Poynting‐Robertson Drag: New Analytical and Numerical Solutions

Abstract: The effect of solar or stellar radiation on dust particles' trajectories (the Poynting-Robertson drag) has been studied by a number of authors and applied to interplanetary dust dynamics in numerical computations. Meanwhile some important features of dust flows can be studied analytically by implementing our novel hydrodynamical approach to use the continuity equation written in the particle's orbital elements as coordinates (Gor'kavyi, Ozernoy, & Mather 1997). By employing this approach and integrating the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…The flux of meteoroids with m > 10 −5 g is lower in IMEM than in the Grün model since the impact velocities of big meteoroids are higher at 1 AU from the Sun in IMEM and they produce larger craters on the lunar rocks than in the Grün model, which assumed a single impact velocity for all meteoroid sizes. evolutionary paths (Gor'kavyi et al 1997). Their distributions are also established theoretically in IMEM, with the normalization factors being inferred from the fit to observations.…”
Section: Imemmentioning
confidence: 94%
See 2 more Smart Citations
“…The flux of meteoroids with m > 10 −5 g is lower in IMEM than in the Grün model since the impact velocities of big meteoroids are higher at 1 AU from the Sun in IMEM and they produce larger craters on the lunar rocks than in the Grün model, which assumed a single impact velocity for all meteoroid sizes. evolutionary paths (Gor'kavyi et al 1997). Their distributions are also established theoretically in IMEM, with the normalization factors being inferred from the fit to observations.…”
Section: Imemmentioning
confidence: 94%
“…One would expect a similarly shaped "edge-brightened" radial density with the peaks at the perihelion and aphelion distances of the parent body orbit (e.g., Sect. 3 in Gor'kavyi et al 1997). However, the dust in asteroid bands is proven to be migrating toward the Sun under the PoyntingRobertson drag; Reach (1992) has demonstrated that the temperatures of particles and parallaxes of the bands measured from the moving Earth are both higher than those expected in the respective asteroid families of their origin, implying that the bands extend farther toward the Sun than their ancestor bodies.…”
Section: The Kelsall Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a planet, the surface density of dust between the star and the pericenter of dust sources is constant, while the number density of dust varies as r-1 , r being heliocentric distance (Gorkavyi et al 1997). The presence of a planet induces dramatic changes in the cometary and dust distribution.…”
Section: Modelling /3 Pictoris Disk With Embedded Planetmentioning
confidence: 99%
“…Moreover, Gor'Kavyi et al [9,10] used a continuum approach in orbital element space serving as a tool to analyse the transport of interplanetary dust grains as well as their long-term dynamical evolution.…”
Section: Introductionmentioning
confidence: 99%